Impact of pulsed UV‐B stress exposure on plant performance: How recovery periods stimulate secondary metabolism while reducing adaptive growth attenuation. (13th August 2018) - Höll, Janine; Lindner, Sonja; Walter, Hannah; Joshi, Drishti; Poschet, Gernot; Pfleger, Sina; Ziegler, Tobias; Hell, Rüdiger; Bogs, Jochen; Rausch, Thomas
Abstract: Upon continuous stress exposure, plants display attenuated metabolic stress responses due to regulatory feedback loops. Here, we have tested the hypothesis that pulsed stress exposure with intervening recovery periods should affect these feedback loops, thereby causing increased accumulation of stress‐induced metabolites. The response of Arabidopsis plantlets to continuous UV‐B exposure (Cuv ) was compared with that of pulsed UV‐B exposure (Puv ). The differential responses to Puv versus Cuv were monitored at the level of gene expression and metabolite accumulation, using wild type (WT) and different mutant lines. In comparison with Cuv, Puv increased sinapyl and flavonol (S + F) content, whereas adaptive growth attenuation was reduced. Furthermore, in a myb4 mutant (AtMYB4, repressor‐type R2R3‐MYB transcription factor), the S + F content was increased only for Cuv, but not beyond the level for Puv observed in WT. These observations and the ability of AtMYB4 to repress AtMYB12/AtMYB111‐mediated activation of target gene promoters ( pCHS and pFLS ) indicate that the increase of S + F content after Puv observed in WT plants results from reduced feedback inhibition by AtMYB4. The results support the notion that stress‐induced metabolic changes not necessarily cause a growth penalty. Furthermore, the observed Puv ‐induced increase in flavonol accumulation may stimulate reevaluation of commercial plant production practices. Abstract : Attenuation of plant secondary metabolite accumulation in response to continuous stress exposure is thought to depend on regulatory feedback loops. This study explores to what extent intervening stress‐free recovery periods can dampen these negative feedback loops. Treatment of Arabidopsis seedlings to UV‐B light revealed that pulsed stress exposure results in increased flavonol accumulation as compared with continuous exposure. Analysis of various mutant lines indicates that this phenomenon is due to a modified action of the transcriptional repressor AtMYB4.